What is Vitamin D Deficiency Dangerous and How to Diagnose it - Isroilova Guljannat Pardabaevna (Peerian Journals Publishing, 2022)
For most people, vitamin D is linked to the bones—given in the form of fish oil to children to prevent rickets, and TV commercials recommend it to the elderly to protect them from osteoporosis.
Keywords: Vitamin D; calcium; diseases; deficiency